PKM Empowerment and Preservation of Local Cultural Arts of Bali Dewi Ratih Dance Studio in Banjar Busana Kaja, Baha Village, Mengwi Sub-District, Badung District - Desak Gde Dwi Arini; Putu Ayu Sriasih Wesna; Ni Ketut Sukiani; Putu Dyah Agung Mas Narayana (Fakultas Hukum, Universitas Warmadewa, 2023)
As an institution of higher education, Warmadewa University must ensure that it always obeys the Tridharma of Higher Education in accordance with the vision and mission that has been determined. Now every lecturer is encouraged to be able to package community service activities both in groups and individually which will show concern for the community. Community service activities can be carried out by enlightening by providing legal counseling and consultation and assistance to the community in various fields of life in the economic field. Empowerment, preservation and legal protection of Dewi Ratih Balinese Dance Studio in Banjar Busana Kaja, Baha Village, Mengwi District, Badung Regency are very important to maintain the existence of an art studio and keep their work from being claimed by other parties. With the issuance of the operational permit for Dewi Ratih Busana Kaja Dance Studio in 2019, therefore through the community partnership program, the PKM Team of the Faculty of Law, Warmadewa University Denpasar provided assistance in drafting a cooperation agreement with other parties. This aims to have authentic evidence that the Balinese dance studio Dewi Ratih is officially an association of organizations with legal status. In addition, as a legal entity, Dewi Ratih Balinese dance studio in Banjar Busana Kaja has rights and obligations as a legal subject, which will be entitled to receive cooperation with other parties and grant programs from both private and government parties.